One-pot synthesis of grafted brush copolymers via a chain-growth radical/oxidative dual polymerization system. Issue 114 (2nd November 2015) - Govindaiah, Patakamuri; Kim, Yong Seok; Hong, Jae Keun; Kim, Jung Hyun; Cheong, In Woo
Abstract : Grafted brush copolymers via one-step metal-catalyzed chain-growth radical/oxidative dual polymerization. Abstract : This article describes the facile synthesis of grafted brush copolymers via the combination of metal-catalyzed chain-growth radical polymerization and oxidative polymerization, using a dual functional monomer. The most significant finding was the possibility of performing free-radical polymerization and oxidative polymerization in a single step, using copper bromide as a recyclable catalyst. Cu + initiated the radical polymerization via a chain growth mechanism, and Cu 2+ initiated the oxidative polymerization, leading to grafted brush copolymers in which π-conjugated polymers formed the main chains and poly(styrene sulfonate) (PSS) formed the high-density brushes. Nuclear-magnetic-resonance and Fourier-transform-infrared spectroscopic analyses revealed the formation of poly(thiophene)- co -poly(styrene sulfonate) (PTh- co -PSS) and poly(3, 4-ethylenedioxythiophene)- co -polystyrene sulfonate (PEDOT- co -PSS). Ultraviolet and photoluminescence analyses confirmed the formation of the π-conjugated polymers during the dual polymerization process. These grafted brush copolymers had exceptionally good solubilities in N, N -dimethylformamide.